2022
DOI: 10.1016/j.ijbiomac.2022.01.108
|View full text |Cite
|
Sign up to set email alerts
|

Review: A systematic review of virus-like particles of coronavirus: Assembly, generation, chimerism and their application in basic research and in the clinic

Abstract: Virus-like particles (VLPs) are nano-scale particles that are morphologically similar to a live virus but which lack a genetic component. Since the pandemic spread of COVID-19, much focus has been placed on coronavirus (CoV)-related VLPs. CoVs contain four structural proteins, though the minimum requirement for VLP formation differs among virus species. CoV VLPs are commonly produced in mammalian and insect cell systems, sometimes in the form of chimeric VLPs that enable surface display of CoV epitopes. VLPs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 159 publications
(219 reference statements)
0
6
0
Order By: Relevance
“…Since the novel coronavirus SARS-CoV-2, there has been an increasing interest in reviewing VLPs as a powerful approach to producing vaccines and nanocarriers [ 20 ]. However, there is a need to complement those studies and recent ones [ 21 ], with basic principles about expressing, manipulating, functionalizing, and characterizing VLPs.…”
Section: Introductionmentioning
confidence: 99%
“…Since the novel coronavirus SARS-CoV-2, there has been an increasing interest in reviewing VLPs as a powerful approach to producing vaccines and nanocarriers [ 20 ]. However, there is a need to complement those studies and recent ones [ 21 ], with basic principles about expressing, manipulating, functionalizing, and characterizing VLPs.…”
Section: Introductionmentioning
confidence: 99%
“…Since the SARS-CoV-2 structural proteins N, M, Orf3, Orf7a and Orf7b interact with both Hsp90 isoforms, we hypothesized that Hsp90 affects the viral assembly process. Thus, we focused all remaining experiments on the M and N proteins, which are the minimal requirement for SARS-CoV-2 virus-like particle (VLP) formation ( 28 , 29 , 30 ). We also performed binding assays to test whether Hsp90 participates in the interaction between viral M and N proteins in the following study, as M-N interaction is also essential for SARS-CoV-2 virion assembly ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported the production of CoV-like particles using the baculovirus-insect cell expression system (BEVS) [ 27 ]. PEDV, IBV, and SARS-CoV-2 VLPs were successfully prepared by co-expression of S, E, and M proteins in Sf9 insect cells, with shapes and sizes similar to those of the naive virus.…”
Section: Discussionmentioning
confidence: 99%